Comparing the effectiveness of Internet advertising to other IMC mix components. - Tan, Dai Shij. (2008)
Within the last two years, the Internet registered the most rapid growth (i.e., ad revenue, number of users using the medium etc) among media, followed by an abrupt withdrawal of investments as criticisms built up. To better conceptualize its impact, this research positions Internet advertising as a component of the Integrated Marketing Communications (IMC) mix.